2010
DOI: 10.7150/ijms.7.240
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Hidradenitis Suppurativa

Abstract: Background: Hidradenitis suppurativa (HS) is a chronic, relapsing inflammatory disease of skin, characterized by recurrent draining sinuses and abscesses, predominantly in skin folds carrying terminal hairs and apocrine glands.Method: This study reviewed 54 sites in 27 patients with moderate to extensive chronic inflammatory skin lesions treated surgically in our hospital from 2004 through 2009, with a follow-up of at least 6 months.Result: A total number of 54 operative procedures were performed during the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 17 publications
0
72
0
4
Order By: Relevance
“…16 Other recent studies have also reviewed results of the available musculocutaneous and fasciocutaneous flap repairs. 14,17 In 2010, Menderes published results for 27 patients, which included 16 patients (23 axillae) who underwent a wide local axillary excision for HS, and reported no disease recurrence. Ten axillae were repaired primarily, and 13 with fasciocutaneous or musculocutaneous flaps.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…16 Other recent studies have also reviewed results of the available musculocutaneous and fasciocutaneous flap repairs. 14,17 In 2010, Menderes published results for 27 patients, which included 16 patients (23 axillae) who underwent a wide local axillary excision for HS, and reported no disease recurrence. Ten axillae were repaired primarily, and 13 with fasciocutaneous or musculocutaneous flaps.…”
Section: Discussionmentioning
confidence: 98%
“…6,12 The literature advocates wide local excision of the diseased tissue, but does not define what constitutes adequate tissue removal. 3,7,9,[13][14][15] Morgan et al 15 have used an atropine/oxytocin/iodine method to define apocrine gland-bearing tissue and demarcate the area of excision. On average, this was an 11 × 8 cm area for the axilla.…”
Section: Discussionmentioning
confidence: 99%
“…15 Another fasciocutaneous perforatorYbased flap for closure of sacrococcygeal defects is the fasciocutaneous V-Y flap which has such advantages as providing local healthy tissue without impairing muscle function. 16 Nevertheless, the major disadvantages of this flap are that it requires a scrutinized dissection and they usually fail to achieve a tension-free closure of the large sacrococcygeal defects. Yunqin et al 17 has reported pediceled fasciocutaneous flap of multi-island design for large sacral defects.…”
Section: Discussionmentioning
confidence: 99%
“…5 The most frequently isolated microorganisms are: Proteus mirabilis, Staphylococcus aureus, and Escherichia coli. 6 Diagnosis is difficult if there is no experience with the disease, and therefore it tends to become chronic and extend from the involved area. 7 The concept of hidradenitis suppurativa is not new, but its etiology is unknown, 8 and so the following was concluded upon analyzing the present case:…”
Section: Enfermedad De Verneuil Presentación De Un Caso Y Revisión Dmentioning
confidence: 99%